Environmental Particle Emissions due to Automated Drilling of Polypropylene Composites and Nanocomposites Reinforced with Talc, Montmorillonite and Wollastonite - Starost, K; Frijns, E; Laer, J V; Faisal, N; Egizabal, A; Elizextea, C; Nelissen, I; Blazquez, M; Njuguna, J (IOP conference series. Materials Science and Engineering, 2017)
In this study, the effect on nanoparticle emissions due to drilling on Polypropylene (PP) reinforced with 20% talc, 5% montmorillonite (MMT) and 5% Wollastonite (WO) is investigated. The study is the first to explore the nanoparticle release from WO and talc reinforced composites and compares the results to previously researched MMT. With 5% WO, equivalent tensile properties with a 10 % weight reduction were obtained relative to the reference 20% talc sample. The materials were fabricated through injection moulding. The nanorelease studies were undertaken using the controlled drilling methodology for nanoparticle exposure assessment developed within the European Commission funded SIRENA Life 11 ENV/ES/506 project. Measurements were taken using CPC and DMS50 equipment for real-time characterization and measurements. The particle number concentration (of particles <1000nm) and particle size distribution (4.87nm - 562.34nm) of the particles emitted during drilling were evaluated to investigate the effect of the silicate fillers on the particles released. The nano-filled samples exhibited a 33% decrease (MMT sample) or a 30% increase (WO sample) on the average particle number concentration released in comparison to the neat polypropylene sample. The size distribution data displayed a substantial percentage of the particles released from the PP, PP/WO and PP/MMT samples to be between 5-20nm, whereas the PP/talc sample emitted larger particle diameters.